IbM PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN PADA UKM CARANG MAS DI DESA KUCUR MALANG - Purnomo, '; Setiawan, Rudy; Yuswanto, ' (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
Small and Medium Enterprises (SMEs) Snack Carang Mas is one form of business that is able to give a positive contribution to economic growth in the village of Kucur. Coconut mas mask food is one of the SMEs that become uggulan in Kucur Village, Dau District, Malang Regency that can not be separated from the problem. The problem is that there are processed production and governance management still using traditional and manual way, making it difficult to increase the quantity of production. Problems of production and marketing process can not be improved maximally. Currently the capabilities and knowledge of human resources of small and medium enterprises (SMEs) are still very limited, especially in the field of administration and finance, so that in their business processing often experience obstacles. This activity aims to assist the preparation of financial statements and form a small business that is productive through the mastery of computer technology or microsof office (Word or excel). With the mastery of the production process and IT is expected production and marketing processes can be optimized.